Bella Tuscany the sweet life in Italy - Mayes, Frances (New York, NY Broadway books, 1999)
The author, having spent several summers working to restore the villa she purchased in Tuscany, shares her ongoing love affair with her home and the country, and discusses her joyous experience of the spring season in Italy.
Primavera -- Bitter greens of Tuscan spring -- Sfuso : loose wine -- Following spring : the palms of Sicily -- A Sicilian menu -- Resurrection -- Following spring : the watery Veneto -- Deeper into the country -- The root of paradise -- Spring kitchen -- Circles on my map : Monte Oliveto Maggiore -- Bagno Vignoni and Pienza -- A loop around Lago Trasimeno -- From a yellow book : thinking of travel -- AP -- Breathing art -- Mad July : the humming urn -- Lost in translation -- Anselmo's idea of tomatoes -- Cold -- Ritmo = Rhythm.
Keywords: Tuscany (Italy) -- Description and travel; Tuscany (Italy) -- Social life and customs